In Vivo Study of the Anticancer Activity of Doxorubicin Loaded on a Cellulose-Based Nanocarrier System - Tiba Majid Hammed; Ashour Hamood Dawood; Inaam Sameh Arif; Yahya Dreaim Saihood (College of Pharmacy / Mustansiriyah University, 2018)
Many cancer treatment protocols regard doxorubicin as a one of the most effective anticancer agents available to treat different types of cancer. Its mechanisms of action include either intercalation with the DNA of the cancerous cells, production of reactive oxygen species ROS or it acts by inhibition of topoisomerase TOP IIα. The international administration of doxorubicin is associated with a real problem which is cancer cells resistance, which is a worldwide problem that reduced its usage. Therefore, in this study doxorubicin was loaded on a cellulose-based nanocarrier system [Cellulose Nanowhiskers (CNWs)] as an attempt to increase its intracellular concentration and reduce its resistance. The effect of the loaded doxorubicin was evaluated by measuring the reduction in the size of the tumor masses those induced by intra peritoneal administration of adenocarcinoma cells (AM3) to a group of albino mice. This study was performed in comparison with unloaded doxorubicin and it was found that the loaded doxorubicin produced a significant reduction in tumor size with suspended antitumor effect compared to the unloaded doxorubicin.